Inventory and Conservation Status of Herpetofauna Species at Tapos Resort, Gunung Gede Pangrango National Park - Muhamad Rafi Al Gifari; Muhammad Daffa Hasyalillah; Muhammad Saltes Albiansyah; Muhammad Fazly Mawla; Rafi Hilman Al Ghiyasi; Ahmad Syafiq Bainahum; Mikail Abdul Rozaq; Rafi Hilman Al Ghiyasi; Fatihatsal Murfi; Narti Fitriana; Dinda Rama Haribowo (Jurnal Biologi Tropis, 2026)
Herpetofauna is a group of reptiles and amphibians. Gunung Gede Pangrango National Park (TNGGP) has a diverse range of herpetofauna. This study aims to record and inventory the conservation status of herpetofauna in the Tapos Resort area of Gunung Gede Pangrango National Park. Herpetofauna data collection was carried out in the Gunung Gede Pangrango National Park (TNGGP) area, in the Lebak Bumi Ciherang (LBC) forest block and the Cinakimun forest block. West Java, Ciawı District, Bogor Regency, West Java Province. The methods used were Visual Encounter Survey (VES) and Hand Searching. Based on the observation results, a total of 39 individuals were recorded, consisting of 2 orders, 9 families, 10 genera, and 12 species. The most commonly found species in the order Anura was Microhyla achatina with 6 individuals, while in the order Squamata it was Cyrtodactylus marmoratus with 9 individuals. The conservation status according to the IUCN for all species found is Least Concern. Further research is recommended to add to the list of herpetofauna in the Tapos Resort area that have not yet been found.